Understanding long-serving millennial early childhood teachers: what motivates them to stay in the teaching profession - Ong, Joanna Mary C. (Animo Repository, 2022)
This research study examined millennial early childhood teachers who have been in the teaching profession for at least ten years. Five case studies were conducted for this study to understand and analyze what motivates the teachers to stay in the teaching profession. Data findings revealed that there are two main themes of motivation for the long-serving millennial early childhood teachers to stay teaching. These are The Joy of Teaching and Work Environment. Specifically, under the theme of The Joy of Teaching, the categories of Affinity for Children, and Sense of Purpose and Fulfillment were discovered for all five teacher participants. On the other hand, under the Work Environment theme, the Relationship in the Workplace is the top motivation for these five teachers to stay in the profession. Likewise, this research study also discovered some of the hindrances that could make the teachers leave the profession. Among the top hindrances are Financial Needs, Issues with Parents, and School System. Furthermore, some recognizable qualities of the millennial early childhood teachers were also revealed from this research study. These qualities include being confident, passionate, has a strong personality, being an effective teacher, has a learner-centered perspective, possesses content and curriculum knowledge, life-long learner, diligent, dedicated, multi-tasker, values work-life balance, warm and caring, and patient.